ChemInform Abstract: Promotion Effect of Constituents from the Root of Polygonum multiflorum on Hair Growth. Issue 2 (14th January 2014) - Sun, Ya Nan; Cui, Long; Li, Wei; Yan, Xi Tao; Yang, Seo Young; Kang, Jung Il; Kang, Hee Kyoung; Kim, Young Ho
Abstract isolation of the two new compounds (I) and (II) along with eight known compounds and evaluation of their promotion effects on hair growth